2001
DOI: 10.1002/syn.1035
|View full text |Cite
|
Sign up to set email alerts
|

D2 but not D3 receptors are elevated after 9 or 11 months chronic haloperidol treatment: Influence of withdrawal period

Abstract: Previous postmortem studies have identified divergent alterations in D2 and D3 receptors in schizophrenia but those results cannot be interpreted without further understanding of whether antipsychotic regulation of the D3 receptor is different from that of the D2 receptor. Depot parenteral administration of haloperidol decanoate was utilized to achieve consistent high levels in rat brain for 9 months with 2-month withdrawal or 11 months with 48-h withdrawal and compared to vehicle control and acute haloperidol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 51 publications
0
26
1
Order By: Relevance
“…Changes in dopamine signaling must therefore be involved. It has been proposed that withdrawal from antipsychotic treatment induces dopamine supersensitivity by increasing striatal D 2 receptor number (Burt et al, 1977;Muller and Seeman, 1977;Clow et al, 1980;Seeman, 1980;Fleminger et al, 1983;Joyce, 2001). Both haloperidol doses we tested led to a supersensitive locomotor response to amphetamine, but only the higher dose increased striatal D 2 receptor number.…”
Section: Discussionmentioning
confidence: 63%
“…Changes in dopamine signaling must therefore be involved. It has been proposed that withdrawal from antipsychotic treatment induces dopamine supersensitivity by increasing striatal D 2 receptor number (Burt et al, 1977;Muller and Seeman, 1977;Clow et al, 1980;Seeman, 1980;Fleminger et al, 1983;Joyce, 2001). Both haloperidol doses we tested led to a supersensitive locomotor response to amphetamine, but only the higher dose increased striatal D 2 receptor number.…”
Section: Discussionmentioning
confidence: 63%
“…These differences in competition of clozapine against endogenous dopamine could contribute to the abovementioned regional differences of concentration/occupancy curves. Additionally, upregulation of D 2 but not D 3 receptors under antipsychotic treatment together with different spatial distributions of D 2 and D 3 receptors may contribute to the described observations (Joyce, 2001).…”
Section: Discussionmentioning
confidence: 88%
“…Calculation of receptor occupancy for a brain region with reduced receptor numbers from a comparison with normal volunteers should lead to overestimation of the occupancy, not underestimation. However, if D 2 and D 3 receptors are differentially regulated by clozapine in selected brain regions, or if D 2 and D 3 receptors are differentially regulated in patients with schizophrenia and normal controls, then the estimation of occupancy values in patients from comparison with normative values obtained in healthy subjects might be misleading (Gurevich et al, 1997;Joyce, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…(Malmberg et al, 1993), it is unlikely that the increased [ 11 C]raclopride binding seen after haloperidol reflects increased D 3 -receptor densities. Indeed, previous studies have shown that whereas chronic haloperidol increases D 2 -receptor density, it does not affect D 3 -receptor density in the rat striatum (Levesque et al, 1995;Florijn et al, 1997;Joyce, 2001).…”
Section: Discussionmentioning
confidence: 97%